2020
DOI: 10.1152/japplphysiol.00468.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to rhythmic handgrip exercise in heart failure with preserved ejection fraction

Abstract: While the contribution of non-cardiac complications to the pathophysiology of heart failure with preserved ejection fraction (HFpEF) have been increasingly recognized, disease-related changes in peripheral vascular control remain poorly understood. We utilized small muscle mass handgrip exercise to concomitantly evaluate exercising muscle blood flow and conduit vessel endothelium-dependent vasodilation in individuals with HFpEF (n = 25) compared to hypertensive controls (HTN) (n = 25). Heart rate (HR), stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 91 publications
3
17
0
Order By: Relevance
“…Only very few studies have investigated hemodynamic and metabolic variables in HFpEF patients during isolated forearm and knee-extensor exercise. In one study, skeletal muscle vascular conductance and blood flow were found to be reduced at higher submaximal intensities in patients in the absence of macrovascular dysfunction and dysregulated central hemodynamics ( Ratchford et al, 2020 ). In another study, a-vO 2 difference was reduced across all brachial blood flows in patients, however, peak O 2 uptake was preserved in HFpEF through a statistically non-significant enhancement (∼14%) of blood flow ( Zamani et al, 2020 ).…”
Section: Effect Of Aging and Cardiometabolic Diseases On The Matching...mentioning
confidence: 99%
“…Only very few studies have investigated hemodynamic and metabolic variables in HFpEF patients during isolated forearm and knee-extensor exercise. In one study, skeletal muscle vascular conductance and blood flow were found to be reduced at higher submaximal intensities in patients in the absence of macrovascular dysfunction and dysregulated central hemodynamics ( Ratchford et al, 2020 ). In another study, a-vO 2 difference was reduced across all brachial blood flows in patients, however, peak O 2 uptake was preserved in HFpEF through a statistically non-significant enhancement (∼14%) of blood flow ( Zamani et al, 2020 ).…”
Section: Effect Of Aging and Cardiometabolic Diseases On The Matching...mentioning
confidence: 99%
“…Therefore, brachial artery vasodilation during progressive handgrip exercise can be used as a measurement of endothelium-dependent dilation. Our group has utilized this ‘sustained stimulus flow-mediated dilation' in a variety of populations to detect endothelial dysfunction in both health and disease ( 8 , 13 , 33 , 34 ), and importantly, have identified the NO-dependent nature of brachial artery vasodilation using this experimental model ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively, few studies have quantified the vasodilatory response to exercise in HFpEF patients. Previously, a series of investigations identified severe reductions in the leg and forearm vascular conductance during exercise in HFpEF that are not attributable to disease‐related decrements in cardiac or conduit arterial dysfunction (Lee, Barrett‐O'Keefe, Nelson, et al, 2016 ; Ratchford et al, 1985 ; Ratchford et al, 2019 ). These findings are in line with findings of microvascular dysfunction and skeletal muscle structural and oxidative deficiencies in HFpEF (Kitzman et al, 2014 ; Zamani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%